KADAR KOLESTROL DARAH PADA IBU PENDERITA DISLIPIDEMIA YANG DIBERI NIASIN - Almasyhuri Almasyhuri; Ance Murdiana; Susie S. Suwardi; Joko Pambudi; Heni Komalasari (Persagi, 1998)
A study on niacin supplementation has been conducted on women with cholesterol level between 200-250 mg/dl. The objective of this study was to see the effect of niacin supplementation on cholesterol, triglyceride and low density lipoprotein (LDL) levels. Twenty two respondents were divided into two groups. The first group, nine respondents, were given niacin 2x75 mg and the second group, 13 respondents, were given lactose 2x75 mg as placebo. Data collected included antropometry, side effects and clinical status. Analysis of blood for cholesterol and LDL was done using CHOD-PAP method, whereas analysis of triglyceride was done using GPO-PAP method. The results of this study showed that cholesterol and LDL levels decreased significantly 11,0% and 18,9% respectively, after one week supplementation and remained in that level two weeks afterwards. Triglyceride level decreased in all groups after two weeks but the difference was not significant.Keywords: cholesterol, triglyceride, low density lipoprotein (LDL), niacin.